Stable Field Emission from Layered MoS2 Nanosheets in High Vacuum and Observation of 1/f Noise - Ranjit V. Kashid; Pracheetee D. Joag; M. Thripuranthaka; Chandra S. Rout; Dattatray J. Late; Mahendra A. More (Nanomaterials and Nanotechnology)
Field emission and current noise of hydrothermally synthesized MoS2 nanosheets are investigated in ultra- high-vacuum and industrially suited high-vacuum conditions. The study reveals that the emission turn-on field is pressure dependent. Moreover, the MoS2 nano‐ sheets exhibit more stable field-electron emission in high- vacuum than in ultra-high-vacuum conditions. The investigations on field-emission current fluctuations show features of 1/f-type noise in ultra-high-vacuum and high- vacuum conditions, attributed to adsorption and desorp‐ tion processes. The post-field-emission results indicate the MoS2 nanosheets are a robust field emitter in high- vacuum conditions.